Abdominal Wall Thickness is a Predictor for Surgical Site Infections in Patients Undergoing Colorectal Operations. Issue 7 (July 2021) - Chang, Yu-Wei W.; Murphy, Kyle; Yackzan, Daniel; Thomas, Sarah; Kay, Danielle; Davenport, Daniel; Evers, Bernard M.; Bhakta, Avinash S.
Background: Surgical site infections (SSIs) are an established complication following colorectal operations, with rates up to 30% reported in the literature. Obesity is a known risk factor for SSI; however, body mass index (BMI), body fat percentage, waist-hip ratio, or abdominal circumference are imperfect measures. The purpose of our study was to determine whether abdominal wall thickness (AWT) is predictive of SSI. Methods: We queried our American College of Surgeons National Surgical Quality Improvement Project (ACS-NSQIP) database for patients (age ≥18 years) undergoing a colectomy at the University of Kentucky (UK) from January 1, 2013 to December 31, 2018. The exclusion criteria included patients with open abdomens or the lack of preoperative computed tomography (CT) within 3 months of their operation. AWT was measured at the level of the anterior superior iliac spine (ASIS) on abdominal CT. SSI was defined by superficial SSI, deep SSI, and wound dehiscence. Results: Of 1261 patients enrolled, 52.2% were female, with an average age of 57.4 years. More patients had laparoscopic operations (51%), and the median length of stay was 7 days. Our study demonstrated an SSI rate of 9.4% and a 30-day readmission rate of 11%. The overall mean AWT was 2.6 cm (range .1-13.1), and patients with the highest AWT quintile were more likely to develop an SSI than the lowest quintile (12% vs. 5%). After controlling for risk factors and confounders, the odds of an SSI were 3.6 times higher for patients with the highest AWT than patients with the lowest AWT. Conclusions: Among colorectal surgery patients, AWT is an independent risk factor predictive for SSI.